Soto ayam Pak Yatno film by Nurina Malinda, Yeah Seng Guan. - Malinda, Nurina (2010)
Early each morning, Pak Yatno and his friends sell "soto ayam", a popular Indonesian dish, on the bustling sidewalks of Yogyakarta City. They are part of a vending community that work under a patron. This film offers a glimpse into their routines and experiences.